2015
DOI: 10.1161/circulationaha.114.010988
|View full text |Cite
|
Sign up to set email alerts
|

Control of the T Follicular Helper–Germinal Center B-Cell Axis by CD8 + Regulatory T Cells Limits Atherosclerosis and Tertiary Lymphoid Organ Development

Abstract: Background-The atheromodulating activity of B cells during the development of atherosclerosis is well documented, but the mechanisms by which these cells are regulated have not been investigated. Methods and Results-Here, we analyzed the contribution of Qa-1-restricted CD8 + regulatory T cells to the control of the T follicular helper-germinal center B-cell axis during atherogenesis. Genetic disruption of CD8 + regulatory T cell function in atherosclerosis-prone apolipoprotein E knockout mice resulted in overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
145
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(155 citation statements)
references
References 35 publications
7
145
1
2
Order By: Relevance
“…FoxP3þ CD4 cells constitute a Treg population that is atheroprotective, particularly in experimental settings. Recent data have suggested that there are CD8þ T cells with an immunosuppressive capacity 24 and that such CD8þ Tregs influence atherosclerosis. 24 To shed light on these mechanisms, PBMCs from patients undergoing CEA were used for in vitro analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FoxP3þ CD4 cells constitute a Treg population that is atheroprotective, particularly in experimental settings. Recent data have suggested that there are CD8þ T cells with an immunosuppressive capacity 24 and that such CD8þ Tregs influence atherosclerosis. 24 To shed light on these mechanisms, PBMCs from patients undergoing CEA were used for in vitro analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have suggested that there are CD8þ T cells with an immunosuppressive capacity 24 and that such CD8þ Tregs influence atherosclerosis. 24 To shed light on these mechanisms, PBMCs from patients undergoing CEA were used for in vitro analysis. However, the in vitro system with purified CD4 T cells, CD8 T cells or macrophages did not at all mount the same strong response in IL-10 secretion as that observed in the plaque tissues examined in the ex vivo protocols.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observation of TLOs in the human adventitia of atherosclerotic aorta (10,33), as well as in the adventitia of atherosclerotic mice (8,9), suggests that an adaptive immune response could be mounted within the arterial wall in the adventitia (Figure 1). Indeed, GC B cells, plasma cells and Tfh cells can be found in adventitial TLOs of atherosclerotic ApoE -/-mice, arguing that a humoral immune response might be generated locally (8,29). We recently confirmed that this also is the case in human vascular disease, as the adventitia from atherosclerotic abdominal aortic aneurysms displays TLOs containing Tfh, GC B cells and plasma cells and releases antibodies (29).…”
Section: Where Is This Adaptive Immune Response Generated: Faraway Lymentioning
confidence: 66%
“…Indeed, GC B cells, plasma cells and Tfh cells can be found in adventitial TLOs of atherosclerotic ApoE -/-mice, arguing that a humoral immune response might be generated locally (8,29). We recently confirmed that this also is the case in human vascular disease, as the adventitia from atherosclerotic abdominal aortic aneurysms displays TLOs containing Tfh, GC B cells and plasma cells and releases antibodies (29). The existence of this lymphoid neogenesis in the aorta might impair the efficiency of therapeutic strategies targeting the immune system, such as B2 cell depletion, as it occurs in other chronic inflammatory settings such as chronic graft rejection.…”
Section: Where Is This Adaptive Immune Response Generated: Faraway Lymentioning
confidence: 99%
See 1 more Smart Citation